MAKING SENSE OF SENSE-MAKING IN SPENDING: A QUALITATIVE STUDY - Bustillo, Jacklyn Mae; Lata, Sheryl Mae; Leones, Rhesiane; Vasquez, Michael (President University, 2024)
Making sense on the act of spending is a complicated undertaking in the field of personal finance. Sense-making, in relation to financial expenditure, has emerged as a vital lens to understand the intricacies of spending. Hence, this study investigates the Intra and Extra of spending among the Bachelor of Science in Accountancy (BSA) students of Colegio de la Purisima Concepcion. Specifically, this study explores the intra of spending in terms of preferences and the extra of spending in terms of strategies among the participants as well as any perspective emerging from the constructs being investigated. Using Creswell’s framework on phenomenological research, five graduating BSA students of Colegio de la Purisima Concepcion were purposively chosen to participate following an inclusion criteria. A researcher-made semi-structured interview questionnaire, used to obtain the participant’s perception, underwent content validation. From the data transcripts that were thematically analyzed emerged three themes as regards the sense-making of spending: external force, internal drive, and value-laden. The sense-making of spending involves external force drawn from the recommendations and influences of others. The sense-making of spending signifies internal drive which stemmed from habits, sense of fulfillment, and priorities of the spender. The sense-making of spending purports value-laden which is shaped by perceptions of financial management and the perceived worth ascribed to purchases. The study recommends the creation of a formation program regarding the sense-making capability vis-a-vis students' responsible spending behaviors choices. Future researchers are recommended to explore varied approaches to further investigate sense-making in spending.